SISTEM INFORMASI INVENTARIS BARANG DENGAN BARCODE - Dani Dan; Irwan Irwan; Ahmat Josi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Currently, the information system for the inventory of goods at SMK Negeri 1 Air Gegas, which is mainly in the Regional Public Service Agency (BLUD) in the warehouse section, is still manual, for example recording incoming goods, outgoing goods and calculating stock of goods. Often the officers at the goods custodians have difficulty in collecting data on these goods and make them ineffective. The purpose of developing an inventory information system with barcodes at SMK Negeri 1 Airgegas is expected to be able to improve and make it easier for goods managers, making it easier for report makers. The method used is prototyping, data collection techniques, observation and interviews. In problem analysis at SMK Negeri 1 Airgegas for data collection, goods are still manual, the solution must be computerized. Based on the conclusion that the analysis of the results of the respondents strongly agree with the application made.